A physical description of the adhesion and aggregation of platelets. Issue 4 (12th April 2017) - Chopard, Bastien; de Sousa, Daniel Ribeiro; Lätt, Jonas; Mountrakis, Lampros; Dubois, Frank; Yourassowsky, Catherine; Van Antwerpen, Pierre; Eker, Omer; Vanhamme, Luc; Perez-Morga, David; Courbebaisse, Guy; Lorenz, Eric; et al.
Abstract : The early stages of clot formation in blood vessels involve platelet adhesion–aggregation. Although these mechanisms have been extensively studied, gaps in their understanding still persist. We have performed detailed in vitro experiments, using the well-known Impact-R device, and developed a numerical model to better describe and understand this phenomenon. Unlike previous studies, we took into account the differential role of pre-activated and non-activated platelets, as well as the three-dimensional nature of the aggregation process. Our investigation reveals that blood albumin is a major parameter limiting platelet aggregate formation in our experiment. Simulations are in very good agreement with observations and provide quantitative estimates of the adhesion and aggregation rates that are hard to measure experimentally. They also provide a value of the effective diffusion of platelets in blood subject to the shear rate produced by the Impact-R.